KCa3.1 channels modulate the processing of noxious chemical stimuli in mice. (October 2017) - Lu, Ruirui; Flauaus, Cathrin; Kennel, Lea; Petersen, Jonas; Drees, Oliver; Kallenborn-Gerhardt, Wiebke; Ruth, Peter; Lukowski, Robert; Schmidtko, Achim
Abstract: Intermediate conductance calcium-activated potassium channels (KCa 3.1) have been recently implicated in pain processing. However, the functional role and localization of KCa 3.1 in the nociceptive system are largely unknown. We here characterized the behavior of mice lacking KCa 3.1 (KCa 3.1 −/− ) in various pain models and analyzed the expression pattern of KCa 3.1 in dorsal root ganglia (DRG) and the spinal cord. KCa 3.1 −/− mice demonstrated normal behavioral responses in models of acute nociceptive, persistent inflammatory, and persistent neuropathic pain. However, their behavioral responses to noxious chemical stimuli such as formalin and capsaicin were increased. Accordingly, formalin-induced nociceptive behavior was increased in wild-type mice after administration of the KCa 3.1 inhibitor TRAM-34. In situ hybridization experiments detected KCa 3.1 in most DRG satellite glial cells, in a minority of DRG neurons, and in ependymal cells lining the central canal of the spinal cord. Together, our data point to a specific inhibitory role of KCa 3.1 for the processing of noxious chemical stimuli. Highlights: KCa 3.1 −/− mice show increased behavioral responses to noxious chemical stimuli. KCa 3.1 −/− mice show normal behavioral responses in models of persistent inflammatory and neuropathic pain. KCa 3.1 channel expression in dorsal root ganglia and the spinal cord is mostly localized to non-neuronal cells.